Preparation, in vitro and ex-vivo Evaluation of Mirtazapine Nanosuspension and Nanoparticles Incorporated in Orodispersible Tablets - Hamed, Hiba E.; A. Hussein, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2020)
The objective of the present investigation was to enhance the solubility of practically insoluble mirtazapine by preparing nanosuspension, prepared by using solvent anti solvent technology. Mirtazapine is practically insoluble in water which act as antidepressant .It was prepared as nano particles in order to improve its solubility and dissolution rate. Twenty formulas were prepared and different stabilizing agents were used with different concentrations such as poly vinyl pyrrolidone (PVPK-90), poly vinyl alcohol (PVA), poloxamer 188 and poloxamer 407. The ratios of drug to stabilizers used to prepare the nanoparticles were 1: 1 and 1:2. The prepared nanoparticles were evaluated for particle size, entrapment efficiency, dissolution study, Fourier transform infrared spectroscopy, differential scanning calorimetry, and atomic force microscopy. The percentage of drug entrapment efficiency of F1-F20 was ranged from 78.2% ± 1 to 95.9 % ± 1. The release rate and extent of mirtazapine nanoparticles were inversely proportional to the particle size of the drug i.e. it decreased when particle size increase. It is concluded that the nanoprecipitation have potential to formulate homogenous nanosuspensions with uniform-sized stable nanoparticles of mirtazapine. The prepared nanosuspension showed enhanced dissolution which may lead to enhanced solubility of mirtazapine.